Longitudinal Changes in Magnetic Resonance Imaging–Based Measures of Femorotibial Cartilage Thickness as a Function of Alignment and Obesity: Data From the Osteoarthritis Initiative. Issue 7 (7th June 2017) - Moyer, Rebecca; Wirth, Wolfgang; Eckstein, Felix
Abstract : Objective: To investigate the interaction between malalignment and body mass index (BMI) on cartilage thickness change in patients with knee osteoarthritis (OA). Methods: Femorotibial cartilage thickness was measured from baseline to 2 years in 558 knees with radiographic OA. Cartilage thickness was determined in the central weight‐bearing medial femorotibial cartilage (cMFTC) and lateral (cLFTC) compartments. Femorotibial angle (FTA) was stratified into neutral, minor, and definite malalignment. BMI was stratified using World Health Organization classifications for normal, overweight, and obese. Multivariable linear regression models were used to investigate the interaction between alignment and BMI, adjusting for age, sex, and disease severity. Results: There was no significant interaction for continuous measures of alignment and BMI ( P  = 0.301 for cMFTC and P  = 0.852 for cLFTC). Using BMI tertiles, the association between alignment and medial or lateral cartilage thickness loss was not moderated by BMI, despite a significant association of malalignment with greater cartilage thickness loss ( P  ≤ 0.005). Using FTA tertiles, the association between BMI and medial cartilage thickness loss was approximately 3 times greater in knees with definite malalignment ( P  = 0.149) and approximately 5 times greater in knees with minor malalignment ( P  = 0.006). Specifically, knees with minor varus significantly modified this relationship ( P  = 0.021). Conclusion: Malalignment was significantly associated with cartilage thickness loss per degree increase in malalignment, but was not moderated by BMI. BMI was significantly associated with greater rates of medial cartilage thickness loss per unit increase in BMI but only in knees with minor varus malalignment. These findings have implications for better understanding patient subgroups and intervention strategies targeting risk factors for knee OA.